Fanatisme dan Konformitas Korean Wave pada Remaja - Anisa Agustanti (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2022)
Korean Wave is a term given to the spread of Pop culture in Indonesia at this time, the Korean phenomenon has hit the younger generation, especially Indonesian teenagers, which has many negative impacts. Teenagers must be able to mentally revolutionize and also become agents of change to make Indonesia better, and a part of the period of a complete life journey, namely part of a society that can always make a lot of good contributions, be exalted, optimistic and intelligent. This study uses the Systemic Literature Review method by collecting as many sources as possible, both journals, books related to the research topic. The results of the study show fanaticism and conformity of the Korean wave in adolescents that form loyalty behaviors that are members of groups or communities, the support and attention shown, and beliefs or views that stand out about the object. Teenagers who like the Korean Wave can be tried not to behave in fanaticism and negative conformity such as extreme behavior towards idols, create a community with the same characteristics of liking on the Korean wave and make fanatical behavior and positive conformity of teenagers so that society can accept that.